Early diagnosis and aggressive intervention in Vibrio vulnificus infection following live fish dorsal fin puncture: a case report - Erxiang Zhang; Erxiang Zhang; Zhen Chen; Zhen Chen; Du Feng; Gengfeng Chen; Delong Yin; Delong Yin (Frontiers in Medicine, 2025)
In this paper, we report a case of traumatic wound infection caused by dorsal fin puncture of live fish. A 69-year-old woman developed progressive swelling of her right pinky finger after being stabbed by the dorsal fin of a live fish. The infection was confirmed by bacterial culture as a Vibrio vulnificus infection of a traumatic wound. The patient underwent antibiotic treatment, surgical decompression, debridement, and excision of necrotic tissue. Finally, the right pinkie finger was amputated due to dry gangrene. Early intervention and combined antibiotic therapy led to a good prognosis. As global ocean temperatures rise, the infection rate of this bacterium increases, and vigilance is needed. Clinical practice suggests that such infections should be considered in patients with a history of contact with seafood or seawater; Early diagnosis, active antibiotic therapy and necessary surgical intervention are the keys to improving the prognosis.